Exploring the Thoughts Of H.O.S Tjokroaminoto on National Character Education As A Pillar of Indonesian Transformation - Ilham Samudra Sanur; Soleh Sri Handoyo (Indonesian Journal of Civic and Law Studies (IJCL), 2025)
Character-related issues in Indonesia have become a critical concern affecting the sustainability of social and national life. Therefore, this study aims to explore the educational thought of H.O.S. Tjokroaminoto on character education as a foundation for national transformation. This research employs a qualitative descriptive approach using a literature study method to analyze the key educational concepts proposed by Tjokroaminoto. The findings indicate that Tjokroaminoto emphasized education grounded in moral, spiritual, and nationalistic values as a means of shaping individuals with integrity, religiosity, and a strong sense of national identity. His educational thought remains highly relevant in addressing contemporary educational challenges, including moral crisis, value disorientation, and the potential for social disintegration. Through the internalization of values such as honesty, responsibility, solidarity, and exemplary conduct, character education is viewed as a fundamental strategy for cultivating a young generation that is adaptive, dignified, and capable of competing at the global level without losing its national identity.